Triggering Mechanism for DNA Electrical Conductivity: Reversible Electron Transfer between DNA and Iron Oxide Nanoparticles. (18th February 2015) - Magro, Massimiliano; Baratella, Davide; Jakubec, Petr; Zoppellaro, Giorgio; Tucek, Jiri; Aparicio, Claudia; Venerando, Rina; Sartori, Geppo; Francescato, Federica; Mion, Fabio; Gabellini, Nadia; Zboril, Radek; et al.
Abstract : A new category of iron oxide nanoparticles (surface active maghemite nanoparticles (SAMNs, γ‐Fe2 O3 )) allows the intimate chemical and electrical contact with DNA by direct covalent binding. On these basis, different DNA‐nanoparticle architectures are developed and used as platform for studying electrical properties of DNA. The macroscopic 3D nanobioconjugate, constituted of 5% SAMNs, 70% water, and 25% DNA, shows high stability, electrochemical reversibility and, moreover, electrical conductivity (70–80 Ω cm −1 ). Reversible electron transfer at the interface between nanoparticles and DNA is unequivocally demonstrated by Mössbauer spectroscopy, which shows the appearance of Fe(II) atoms on nanoparticles following nanobioconjugate formation. This represents the first example of permanent electron exchange by DNA, as well as, of DNA conductivity at a macroscopic scale. Finally, the most probable configuration of the binding is tentatively modeled by density functional theory (DFT/UBP86/6‐31+G*), showing the occurrence of electron transfer from the organic orbitals of DNA to surface exposed Fe(III) on nanoparticles, as well as the generation of defects (holes) on the DNA bases. The unequivocal demonstration of DNA conduction provides a new perspective in the five decades long debate about electrical properties of this biopolymer, further suggesting novel approaches for DNA exploitation in nanoelectronics. Abstract : DNA based self‐assembled nanoconjugates and a macroscopic metamaterial are synthetized, using naked maghemite nanoparticles as electroactive supports. DNA nanoconjugates show reversible electrochemical behavior and better electrochemical performances with respect to bare nanoparticles. The intimate contact between DNA and nanoparticles is studied and electron transfer at the interface between nanoparticles and DNA is unequivocally demonstrated by Mössbauer spectroscopy and modeled by density functional theory.